Language and gender : - Sunderland, Jane (Routledge, 2006)
Language and Gender: presents an up-to-date introduction to language and gender includes diverse work from a range of cultural, including non-Western, contexts, and represents a range of methodological approaches gathers together influential readings from key names in the discipline, including: Deborah Cameron, Mary Haas and Deborah Tannen.